SOME ISSUES OF EXECUTION OF THE SURROGACY AGREEMENT - Babajanova Dinara Islamovna (European Science Publishing, 2024)
This article delves into the legal and ethical complexities surrounding surrogacy agreements. It examines the various challenges faced by intended parents, surrogates, and legal practitioners in navigating the surrogacy process. Key issues discussed include the enforceability of surrogacy contracts, the rights of all parties involved, and the implications of differing legal frameworks across jurisdictions. The article also highlights case studies and recent developments in surrogacy law, providing insights into best practices for drafting and executing surrogacy agreements.
Keywords: Surrogacy, Surrogacy Agreement, Reproductive rights, Legal frameworks, Ethical Considerations, Contract Enforceability, Surrogates.